Pembuatan Nugget Ikan Gabus di Desa Bangso Kecamatan Kumpeh Ulu Kabupaten Muaaro Jambi - Metha Monica; Hajar Setyaji; Suryanto Suryanto; Mukhsin Mukhsin (Universitas Pahlawan Tuanku Tambusai, 2023)
human resources, capital, raw materials and mastery of technology Solution: more hygienic production of snakehead fish nuggets. Involved Partners: Contributions as recipients of technology provided by the service team implementer. The fundamental contribution is the Makmur Fisherman Family Group, Bangso Village, Kumpeh Ulu District, Muaro Jambi Regency Results and Discussion: By adding certain food ingredients such as snakehead fish meat into the process of making fish nuggets, biscuits with added value for health, in this case protein, can be produced. Fish As an animal food, it has several advantages compared to other sources of protein, including the relatively high protein content in the body of fish, which is composed of amino acids that are patterned close to the needs of amino acids in the human body. Fish meat contains unsaturated fatty acids needed by the body. man. This activity will be carried out with an emphasis on the active participation method of the target group. The target group involved in this activity is the fishermen's family group (Prosperous Bangso Village). The approach to this method is expected that the target group can master the simple technological processes of processing snakehead fish such as fish nuggets Conclusion The target group for this service is the Makmur fishermen family group. The Makmur Fishermen family group is very happy with this service activity because they can make their own nuggets with a better taste than buying those in the market. So far they know that nuggets are only made from chicken, not snakehead fish, so they can make snakehead fish nuggets because there are many raw materials such as snakehead fish in the Bangso area. The suggestion is that this Community Service in the Bangso area can be made from processed fish products other than fish nuggets such as meatballs, fish sauce, fish paste and others.